At the Conceptual Crossroads of Politics and Technology: An Exploration Into EU Digital Policy - Björk, Anna; Ojanen, Atte; Anttila, Johannes; Mikkonen, Johannes (Cogitatio Press, 2026)
As the EU pursues digital sovereignty and defines its role in the global digital era, this article examines the conceptual politics that shape EU technology policy. By conceptual politics, we refer to how the meanings and applications of core political concepts are actively contested, shaped, and renegotiated within policy discourse and practice. While existing scholarship has examined discursive strategies and technocratic tendencies in EU digital policy in isolation, this article distinctively analyses their paradoxical interplay. We do so by employing a conceptual politics framework that emphasises temporality, drawing insights from conceptual history. We focus on how foundational concepts, including rights, governance, and agency, are being renegotiated at the intersection of EU politics and rapid technological change. Specifically, we examine the conceptual shifts related to two cases—fundamental democratic concepts (digital rights) and those prompted by specific technologies (blockchain)—to illuminate how the discursive framing of digital technologies performs political work. Through our analysis of policy documents, we identify a central tension: as the EU utilises expansive future‐oriented discourse to frame its digital policy, this simultaneously tends to narrow the horizon of expectations and make politics more technocratic. This dynamic risks obscuring the contested nature of politics by framing technological development as inevitable.